JOINT PARENTAL RESPONSIBILITIES AFTER DIVORCE OR SEPARATION IN THEORY AND PRACTICE - Kovaček Stanić, Gordana; Samardžić, Sandra O.; Kovačević, Milica (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
Exercising parental responsibilities can take two forms. On the one hand, parents having parental responsibilities can exercise them jointly. Another possibility is a sole custody arrangement when one parent exercises parental responsibilities alone. Joint exercise of parental responsibilities even in the cases when parents live separately was first introduced into our legal system by the Family Act of 2005. One of the conditions for jointly exercising parental responsibilities in these situations is the written agreement between the parents. This paper gives a review of the case law concerning parental responsibilities after divorce for different periods of time: the reviews of 1969 and of 1979 are given first, followed by the 1987, 1988 and 1989 case law reviews of two courts of first instance – the High Court in Novi Sad and the High Court in Subotica. Finally, the research results on the exercise of parental responsibilities after divorce in 2007 and 2016, conducted at the Basic Court in Novi Sad, are also presented, when a certain number of cases of joint exercise of parental rights are also analyzed, bearing in mind that this form of parental responsibility has existed since 2005, when the Family Act was adopted.